The populistisation of green politics and the greening of populism: an examination of environmental populism in Europe - Cong Fu (International Journal of Anthropology and Ethnology)
Abstract In the face of neoliberalism’s failure and the challenges posed by environmental issues, green politics has found itself at the intersection of populism and environmentalism. Environmental concerns have become integral to populist agendas, emerging as a new form and approach to green politics in Europe. This paper defines environmental populism as the integration of green ideas and associated behavioral patterns within populist ideology and provides a categorized analysis of five ideological types: far-left, left, center, right, and far-right. By analyzing the strategies through which environmental populism exploits structural opportunities within party competition and party systems, it is possible to identify the populistisation of green politics and the greening of populism at the left and right ends of the political spectrum respectively. This paper argues that environmental populism is characterized by a self-centered nature, which presents challenges such as the strengthening of nationalism, the fragmentation and contradiction within green politics, and the undermining of relevant governance mechanisms. However, it also opens opportunities for rethinking environmental democracy politically and cognitively, reassessing the ecological identity of the populace, and fostering a form of green cohesion that transcends narrow politics of “identity.” The populistised environmentalism entails an ongoing exploration of eco-socialism and ecological modernization.